PENGARUH MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, AND REPETITION (AIR) BERBANTUAN APLIKASI KAHOOT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Yani, Juliandri; Minta Ito Simamora; Khoiruddin Matondang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Auditory, Intellectually, and Repetition (AIR) learning model assisted by the Kahoot application on students’ mathematical problem-solving ability and examine its effectiveness in the learning process. This experimental study used a pretest–posttest control group design. The population consisted of 55 tenth-grade students of SMKS Al Washliyah Pasar Senen 2 Medan. Probability sampling selected two classes: experimental (30 students) and control (25 students). Research instruments included problem-solving tests and learning effectiveness questionnaires. Results showed that the experimental class achieved a higher posttest mean score (46.33) than the control class (36.59). A t-test indicated a significant difference (Sig. 0.000 < 0.05). Questionnaire results showed a “very good” category with 87.8% and 85.28% for experimental and control classes, respectively. This proves that applying the AIR model assisted by Kahoot effectively improves students’ mathematical problem-solving ability. This study aims to determine the effect of the Auditory, Intellectually, and Repetition (AIR) learning model assisted by the Kahoot application on students’ mathematical problem-solving ability and examine its effectiveness in the learning process. This experimental study used a pretest–posttest control group design. The population consisted of 55 tenth-grade students of SMKS Al Washliyah Pasar Senen 2 Medan. Probability sampling selected two classes: experimental (30 students) and control (25 students). Research instruments included problem-solving tests and learning effectiveness questionnaires. Results showed that the experimental class achieved a higher posttest mean score (46.33) than the control class (36.59). A t-test indicated a significant difference (Sig. 0.000 < 0.05). Questionnaire results showed a “very good” category with 87.8% and 85.28% for experimental and control classes, respectively. This proves that applying the AIR model assisted by Kahoot effectively improves students’ mathematical problem-solving ability.